Cloud computing deployment model selection using the AHP multi-criteria analysis method - Ramos, Bruno de Azevedo (2023)
Cloud computing is a prominent theme in computing that aims to provide on-demand computing resources over the Internet. Many organizations have already adopted cloud technologies, while others are still analyzing the feasibility of this migration. The objective of this paper is to indicate which cloud computing deployment model is the most appropriate to be adopted in an Information and Communication Technology Board of a public educational institution. To this end, the AHP (Analytic Hierarchy Process) multicriteria analysis method is used to assist in the decision making process. First, based on related works in the literature, the hierarchical structure of criteria and sub-criteria is elaborated, after which questionnaires are applied with the work team to prioritize the factors in levels of importance and then select the alternative. As a result, the security criterion is indicated as the most relevant, followed by availability, scalability and, lastly, cost. The alternative considered as suitable for the board of directors is the hybrid cloud. It is concluded that the AHP method proved efficient to evaluate the complexity of the various criteria involved.